Kecerdasan Emosional dan Dukungan Sosial sebagai Prediktor Kesejahteraan Subjektif Mahasiswa - Bilqis Sherenita Fadhlil Wafi; Rizky Putra Santosa (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2026)
This study aims to examine the influence of emotional intelligence and social support on college students’ subjective well-being. The university phase is often characterized by various academic, social, and emotional demands, which may affect students’ psychological functioning. In this context, emotional intelligence and social support are considered crucial predictors that can enhance students’ subjective well-being. Using a quantitative correlational design, the study involved 197 undergraduate students selected through purposive sampling. Data were collected using the WLEIS, MSPSS, and CSSWQ-R, all of which demonstrated strong validity and reliability. The results showed that emotional intelligence significantly predicted subjective well-being (R² = .454), as did social support (R² = .235). Multiple regression analysis revealed that both variables jointly explained 49.8% of the variance in subjective well-being, with emotional intelligence emerging as the stronger predictor (β = .571) compared to social support (β = .234). These findings indicate that students’ ability to understand and regulate their emotions, along with the perceived availability of supportive social relationships, play an essential role in enhancing their subjective well-being.